PERSEPSI RISIKO PADA PEMERINTAHAN DESA: Sebuah Tinjauan Dari Perspektif Perangkat Desa Di Kabupaten Bandung - Taufik, Nur Imam; Pradesa, Hafid Aditya; Agustina, Iin (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2022)
This study aims to explore the perceptions of risks that arise in village governance from the perspective of village officials. With village officials as the research analysis unit, about 62 village officials from developing villages, developed villages, and independent villages in Bandung Regency participated in this study. The researcher employs an instrument to measure respondents' perceptions of risk in several categories of risk impacts already taken in previous studies: financial, strategic, fraudulent, managerial, and technical related to the management of village government—five dimensions of the risk perception model in village governance. The conceptual framework builds the model. Two-stage confirmatory factor analysis tests the study. The results generally reveal that the managerial risk dimension is the risk with the most significant factor weighting compared to other risk dimensions. Thus, findings of risk, mainly managerial risk, may come from people, property, or processes involved in providing services that government organizations expect or need.